PENGARUH PERSEPSI FRAUD DAN KEPERCAYAAN TERHADAP PENGGUNAAN LAYANAN MOBILE BANKING: (NASABAH BANK UMUM PENGGUNA LAYANAN MOBILE BANKING) - Triana Yuniati; Rachmat Pramukty; Srimarta Siburian (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2022)
This study aims to determine the effect of fraud perception and trust on the use of mobile banking on commercial bank customers who use mobile banking services in Indonesia, Bekasi city. This type of research is descriptive quantitative. The population in this study are commercial bank customers who use mobile banking services for less than six months. The sampling technique used is random sampling, which uses a sample of 60 commercial bank customers who use mobile banking services. The data was obtained from distributing questionnaires via google form to respondents. Data analysis in this study used convergent validity test, discriminant validity test, reliability test, and hypothesis testing. The results of this study indicate that (1) the perception of fraud has a influence on the use of mobile banking services (2) trust has a influence on the use of mobile banking services, and (3) the perception of fraud and trust has a simultaneous influence on the use of mobile banking services.